Control simulation and study of load rejection transient for AP1000. (November 2015) - Wang, Pengfei; Chen, Zhi; Zhang, Rui; Sun, Jian; He, Zhengxi; Zhao, Fuyu; Wei, Xinyu
Abstract: The AP1000 nuclear steam supply system (NSSS) is designed to accept large load rejections without initiating a reactor trip using the reactor power control system, the pressurizer pressure and water level control systems, the feedwater control system, the steam dump control system and the rapid power reduction (RPR) system. This paper presents the dynamic simulation and study of load rejection transients for the AP1000 NSSS. A real-time NSSS simulation platform is developed in Matlab/Simulink environment with implementation of a nodal core model, a three-region non-equilibrium pressurizer model, a nonlinear steam generator model, a feedwater system model, a main steam system model, and the relevant control systems. Based on the simulation platform, three typical load rejection transients from full power (FP) are simulated, including the 50%FP load rejection without RPR, the large load rejection to 25%FP with RPR and the load rejection to house load. The simulation results show that the NSSS control systems can successfully respond to load rejection transients without reactor trip or operation of the pressurizer or steam generator safety valves. Sustained stable operation can be obtained under the condition of the minimum house load due to the proper control system responses. Science the world's first AP1000 plant is being constructed in China, these simulation and analysis results can make us have a better understanding of the load rejection operations and the special steam dump and RPR control systems for AP1000, and offer certain guidance for the engineering practice. Highlights: An AP1000 NSSS load rejection simulation platform is developed in Matlab/Simulink. The steam dump and rapid power reduction systems are implemented in the platform. Load rejection transients including that to house load are simulated and analyzed. Control system performance during load rejection transients is evaluated.